Working with Wendy: A tribute to slow scholarship - Lowther, M.W. (South African Journal of Higher Education, 2018)
This article celebrates a decade long collaboration between an academic developer and a practitioner in the field of the professional development of actuaries. The collaboration is narrated and then the various professional development experiences that emerged are explored using Tronto’s (1993, 2013) framework of an ethics of care. The analysis shows that all the elements of Tronto’s framework are present in the implementation of the work by the actuarial profession, although ways could be considered to deepen attentiveness to the response of the care receiver. The model of authentic and caring Continuing Professional Development could be useful to academic developers in their work with educators who are also practitioners. Regarding the collaboration itself, the analysis suggests that the presence of all five elements of Tronto’s ethics of care contributed to successful and caring scholarship.